2023
DOI: 10.1093/heapro/daac125
|View full text |Cite
|
Sign up to set email alerts
|

Barrier profiles in workplace health promotion in Germany

Abstract: Lay Summary Workplace health promotion (WHP) is often faced with low-participation rates despite high relevance. This limits the potential for creating positive effects for the organization and its staff. Therefore, we investigated the barriers perceived by employees themselves using a representative sample (regarding age, gender and education) in Germany. Data were collected using a quantitative online questionnaire and then analyzed regarding underlying patterns. We found that there are differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The sample consisted only of employees from the private-sector with companies of various industries and sizes (see Results). The questionnaire included questions regarding demographics, DWHP (12 closed and 2 open questions) and 22 questions on perceived barriers to WHP participation (Nöhammer et al ., 2014, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample consisted only of employees from the private-sector with companies of various industries and sizes (see Results). The questionnaire included questions regarding demographics, DWHP (12 closed and 2 open questions) and 22 questions on perceived barriers to WHP participation (Nöhammer et al ., 2014, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…supervisor is against participation) and informational (e.g. the information is not attractive) (Nöhammer et al ., 2014, 2023). Higher perceived barriers to participation in WHP are thought to lead to a higher need for DWHP.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is a novel idea of complex adaptive decision-making that considers the dual demands of organization and individual based on the antecedents and consequences mechanisms of OHW. It meets current needs and ensures smooth implementation and predictability of results (Noehammer et al, 2023). Secondly, it can be said to provide a clearer research perspective for cross-level decisionmaking, specifically considering work characteristics, occupational psychology, physiological activity processes, and organizational response tactics (Aghakhani & Park, 2019;Cao et al, 2021).…”
Section: Theoretical Contribution and Practice Significancementioning
confidence: 99%
“…Tuomi et al (2004) confirmed the role of organizational support in healthy work environments. And the importance of continuous individual involvement was emphasized by Noehammer et al (2023). Breaking away from single empirical management decisions and linking programs closely to practices is key to addressing the well-being challenge.…”
mentioning
confidence: 99%